If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 6c Solving 22 = 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. 22 + -6c = 6c + -6c Combine like terms: 6c + -6c = 0 22 + -6c = 0 Add '-22' to each side of the equation. 22 + -22 + -6c = 0 + -22 Combine like terms: 22 + -22 = 0 0 + -6c = 0 + -22 -6c = 0 + -22 Combine like terms: 0 + -22 = -22 -6c = -22 Divide each side by '-6'. c = 3.666666667 Simplifying c = 3.666666667
| 8(-2x-4)+13=-52 | | x^4+4x^3 -x^2 +16x-20=0 | | 3a+9=4a-1 | | x^3-2x^2+5x-2=0 | | X-2/5=3/x | | 7+0.6y=19 | | 8x=26-50 | | 2x+16=130 | | 89-2x=6x+8 | | 3x+5-9=9 | | 4.2x=-4(0.62-1.2) | | 9x+40=3x+4 | | d-7=524 | | t/7.5=4 | | t/7.5-4 | | -21=n+3-5n | | 3x^2+19x-51=0 | | 1.3x+2.4=7.5 | | X-41.8=-10.3 | | 4(x-1)=2(6-2x) | | 1.4x-5=4.2x+13.2 | | 3y^2+2y+5=38 | | (16-2y)+y=2 | | 4x-4=12-4x | | -10(7n+7)=-560 | | 2h-6/8=1/2 | | 4x-12/34 | | x+90+11=18 | | my+w=9 | | f(x)=(x+5)2 | | -5=8x-6y | | 3y+13=-(y+2) |